2015
DOI: 10.1002/pros.22986
|View full text |Cite
|
Sign up to set email alerts
|

Implications and considerations of thermal effects when applying irreversible electroporation tissue ablation therapy

Abstract: Irreversible electroporation (IRE) describes a cellular response to electric field exposure, resulting in the formation of nanoscale defects that can lead to cell death. While this behavior occurs independently of thermally-induced processes, therapeutic ablation of targeted tissues with IRE uses a series of brief electric pulses, whose parameters result in secondary Joule heating of the tissue. Where contemporary clinical pulse protocols use aggressive energy regimes, additional evidence is supplementing orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…IRE applies electric current to ablate tissue with a small transition zone between treated and non-treated tissue (26…”
Section: Irreversible Electroporation (Ire) and Radiofrequency Ablatimentioning
confidence: 99%
“…IRE applies electric current to ablate tissue with a small transition zone between treated and non-treated tissue (26…”
Section: Irreversible Electroporation (Ire) and Radiofrequency Ablatimentioning
confidence: 99%
“…This has enabled the use of mpMRI to guide focal therapy of prostate cancer through one of several minimally invasive techniques, such as high‐intensity focused ultrasound, cryotherapy, laser ablation, and irreversible electroporation . MRI technology not only allows physicians to reach the focal lesions for therapy but also allows them to monitor the status of treatment in real time via MRI thermometry, which results in accurate tumor damage estimation . The early and limited results for focal therapy are promising; however, these methods are still under development, and large‐scale, multiinstitutional studies are needed to determine their efficacy and side effects.…”
Section: Future Applications Of Mpmrimentioning
confidence: 99%
“…Interestingly it has been shown that this method selectively affects the cell membrane, which becomes permeable if the high voltage is high enough. It thus makes it possible to either introduce non permeant molecules (ions, cytotoxic drugs like bleomycin, DNA plasmids) into living cells, which is referred to as reversible electroporation [3,46] or to kill directly the cells in the targeted region (tumor) by a nonthermal mechanism (this is named irreversible electroporation [11,12,15]. cells (cancerous or not).…”
Section: Introductionmentioning
confidence: 99%